THE EFFECT OF INTER-REGIONAL ECONOMIC INTEGRATION ON THE UZBEKISTAN ECONOMY (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article analyzes Uzbekistan's participation in interregional economic integration and its impact on the country's economy. As a result of the economic relations of Uzbekistan with the CIS, Central Asia and other neighboring countries, the positive and negative effects of the increase in trade volume, the development of transport infrastructure, the flow of foreign investments and labor migration are studied. The article also analyzes the impact of interregional economic integration on the fields of agriculture, energy and technological transfer. At the same time, the issues of economic competition, external economic risks and social inequality arising in the process of integration are also considered. Uzbekistan's participation in economic integration serves to achieve its goals of sustainable development, as well as strengthens the importance of internal economic reforms.
Keywords: interregional economic integration, economy of Uzbekistan, trade, investment, competition, sustainable development, transport and logistics, energy cooperation, labor migration, SWOT analysis, external economic risks, technological transfer, infrastructure development, trade balance, investment environment, competitiveness, agricultural export, socio-economic inequality.